189k views
1 vote
What is the product of the polynomials 3x2 + 3 and 4x2 - 1?

1 Answer

0 votes

Answer:


12x^4 + 9x^2 - 3\\

Explanation:

Firstly, put the two equations side by side:


(3x^2 + 3)(4x^2 - 1)

The FOIL method is very useful in this scenario, the formula is:


(a + b)(c + d) = ac + ad + bc + bd

So plug in the known variables:


3x^2 * 4x^2 = 12x^4\\3x^2 * -1 = -3x^2\\3 * 4x^2 = 12x^2\\3 * -1 = -3


12x^4 - 3x^2 + 12x^2 - 3\\

This simplifies to:


12x^4 + 9x^2 - 3\\

Hope this helps!

User Lytesha
by
7.2k points